Designing a Model of Ambidextrous Leadership Competencies in Social Systems - Maasoumeh Mohtaram; Zahra Pakbaz (Institute of Management fekrenoandish, 2023)
The aim of the current research was to design the competency model related to ambidextrous leadership in social systems; It should be noted that the current research is applied in terms of its purpose, the qualitative research approach and the research method are meta synthesis. To conduct this research, the seven stages of Sandelovski and Barso (2007), which have the necessary comprehensiveness, were used. In order to ensure and validate the search process and achieve the research findings, the expert team consisting of four educational management specialists formed the members of the research meta synthesis team. The sources of research data collection were the existing articles and texts about ambidextrous leadership from 2010 to 2023.The findings of this research showed that the model of ambidextrous leadership competencies includes 32 basic themes in 9 organizing themes with the titles: 1. "Individual competencies";   2. "Communication skills"; 3. "Professional-management skills";       4. "participatory management skills"; 5. "Planning skill and strategic thinking"; 6. "Ability to lead change"; 7. "Inclination to increase knowledge"; 8. "The ability to respond to the environment while paying attention to internal coherence"; 9. "The ability to apply contingency management". It should be noted that the output of this research can be provided to the managers and planners of organizational development in order to consciously develop the capabilities and skills of managers at different organizational levels, knowing the factors that influence ambidextrous leadership competencies. Extended abstract Introduction In the last century, various organizations have experienced amazing changes in their processes and areas of activity. The key mission of organizations, which until the 1960s was to expand the scale of production and focus on the quantity of organizational output, turned to increasing the quality of products and services as well as reducing costs. In this era, the managers of the organization tried to make maximum use of the internal resources and assets of the organization and always improve the productivity and efficiency of their organization. But in the 1990s, with the expansion of the competitive environment between organizations, it became clear to the managers of the organization that in a competitive world, only focusing on productivity and efficiency is not enough to maintain the competitive advantage and also the survival of the organization in the long term; Rather, the flexibility and ability to respond to changes and environmental expectations, as well as paying attention to components such as agility, the capacity to change strategic focus and quick and timely response to the evolving and changing environment, as basic axioms for survival and improving the performance of organizations. They play a key role. Accordingly, in the current world, the ability to discover new and innovative ways to create value has become one of the main axes of the strategic thinking of organization leaders (Gastaldi, Lessanibahri, Tedaldi & Miragliotta, 2022). On the other hand, organizations today are facing the fourth industrial revolution, which the complexity of physical and digital realities has created and expanded a complex and unique competitive environment for organizational activity. (Culot, Nassimbeni, Orzes & Sartor, 2022). In this situation, organizations are under pressure to be efficient in the short term and have a competitive performance, but also to be flexible in the long term and operate with an innovative approach; In other words, organizations must be ambidextrous (Derbyshire, 2014). According to March (March, 1991), duality includes exploitation (managing the current position and resources of the organization) and exploration (adapting to environmental changes and continuous innovation); Ambivalence is the ability of an organization in two dimensions of exploration and exploitation in order to increase its competitive power in complex and changing environments, which requires durability and survival, flexibility, development and maintenance of competitive advantage and exploration of potential opportunities in the environment. (Mom, Chang, Cholakova & Jansen, 2019). In fact, expectations and environmental developments are the factors of pressure on organizations in the direction of moving towards bilateral development; In addition to being completely superior in their current operations and improving their functional areas both in terms of quantity and quality, they also strive to innovate and discover new opportunities (Herzallah, Gutierrez-Gutierrez & Rosas, 2017). Therefore, the existence of ambidextrous leaders who can improve the two basic aspects of improving the organization's performance in the current world, i.e. exploitation and exploration, with competence and acquiring the necessary skills, is considered a competitive advantage and a key factor for success in organizations; By considering the environmental dynamics as well as the internal requirements of the organization, ambidextrous leaders establish a smart balance between the two dimensions of exploitation and exploration; Because they believe that the relationship between leadership behavior and the performance of the organization is not a linear and formulated relationship that works in every situation, but the conscious movement of the organization between construction and innovation, guarantees adaptation to the environment and as a result, improves the performance of the organization (Rosing, Frese & Bausch, 2011). Therefore, knowing the characteristics and competences of ambidextrous leaders is considered a vital necessity to guide the organization in dynamic and changing interactive environments. Therefore, in the present study, an attempt was made to study the available sources and texts about the competencies of ambidextrous leaders, the components related to Ambivalent leadership should be identified and investigated. The output of this work can provide useful information to managers and organizational development planners in order to improve the leadership skills of managers according to organizational and environmental requirements. Theoretical framework Organizational ambidexterity refers to the ability of an organization to simultaneously pay attention to exploration and exploitation; The exploitation aspect means that an organization is cultivating the potentials and capacities that it currently and from the past; However, the exploration aspect deals with the creation of innovation, knowledge and the discovery and use of new resources and capabilities (Stokes, Moore, Moss, Mathews, Smith & Liu, 2015). In the new approaches, it is suggested that the ability to simultaneously pursue the exploitation and exploration and cultivation of these two dimensions in employees is the best way to promote innovation and increase the performance of today's organizations. This argument led to the emergence of ambidextrous structure and ambidextrous leadership (Zarb, De La Robertie & Zouaoui, 2017). Ambivalent leadership is considered a new theory in leadership that was proposed by Rasing, Fars and Bush (2011); In their research, these researchers came to the conclusion that ambidextrous leadership can best stimulate and guide innovation; Because he is able to simultaneously use the exploratory skills and the exploitative skills required for the innovation process. In this style of leadership, the leader's open behaviors support exploratory activities and against the closed behaviors of the leader, they support exploitative activities. Finally, Rasing et al. (2011) have defined ambidextrous leadership by combining the aforementioned behaviors as follows: "The ability to cultivate both exploratory and exploitative behaviors in followers by increasing or decreasing variability in their behavior and being flexible. in changing between these two types of behavior". Methodology The upcoming research is applied in terms of purpose, qualitative research approach and meta-composite research method. The purpose of the present synthesis is to discover the basic findings of various studies in the form of concepts; Therefore, to conduct this research, the seven stages of Sandelovski and Barso (2007), which have the necessary comprehensiveness, were used.